DIGITALIZATION AND EDUCATION: AN ANALYSIS OF PRACTICES AND CHALLENGES IN THE CISCO OF TOLIARA I, MADAGASCAR - Bien-Aimé, Whega Danitsaike; Emynorane, Ralaivao Hanginiaina; Bernard, Koto (Journal of Psychology, 2025)
This study investigates the prospects and challenges of educational digitalization in the CISCO of Toliara I, Madagascar, where digital reforms remain largely at the planning stage. Using a qualitative approach, the study gathers insights from teachers, students, parents, and administrators to examine how digital tools are envisioned, the expectations attached to them, and the factors that hinder their adoption. Current practices in attendance monitoring, examination registration, recordkeeping, and school–family communication are still paper-based, fragmented, and often ineffective in addressing chronic absenteeism, high dropout rates, or irregular examination participation. Participants emphasize the potential value of digital identification cards, centralized servers, automated alerts to parents, and digital student profiles as mechanisms to enhance accountability, transparency, and the overall quality of education. Anticipated outcomes include stronger parental involvement, reduced absenteeism, more reliable regulation of examinations, and better support for remedial initiatives such as Back to School for Learning and Teaching at the Right Level. However, the study also highlights major obstacles, including inadequate infrastructure, unstable electricity and internet access, limited technical capacity, and weak institutional coordination. By capturing both the realities of the existing system and the aspirations for digital reform, the study sheds light on the conditions necessary for digitalization to become a transformative force for educational governance in Madagascar.